2023
DOI: 10.3390/asi6020032
|View full text |Cite
|
Sign up to set email alerts
|

A Distinctive Explainable Machine Learning Framework for Detection of Polycystic Ovary Syndrome

Abstract: Polycystic Ovary Syndrome (PCOS) is a complex disorder predominantly defined by biochemical hyperandrogenism, oligomenorrhea, anovulation, and in some cases, the presence of ovarian microcysts. This endocrinopathy inhibits ovarian follicle development causing symptoms like obesity, acne, infertility, and hirsutism. Artificial Intelligence (AI) has revolutionized healthcare, contributing remarkably to science and engineering domains. Therefore, we have demonstrated an AI approach using heterogeneous Machine Lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Our method offers a full view of a particular site, which enables us to identify the disease, as well as interior areas that have been infected with it. Dermoscopy is the most reliable [ 41 ] and time-effective [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] approach for determining if a lesion is a BCC, MEL, SCC, or MN. A computerized diagnostic approach is required to identify BCC, MEL, SCC, and MN, since the number of confirmed cases of deadly skin cancer is continually growing [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our method offers a full view of a particular site, which enables us to identify the disease, as well as interior areas that have been infected with it. Dermoscopy is the most reliable [ 41 ] and time-effective [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] approach for determining if a lesion is a BCC, MEL, SCC, or MN. A computerized diagnostic approach is required to identify BCC, MEL, SCC, and MN, since the number of confirmed cases of deadly skin cancer is continually growing [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…These images were represented by bkl, mel, and nv. Krishnaraj et al [ 52 ] designed machine learning [ 53 , 54 , 55 , 56 ] classifiers that identified binary classes of cervical cancer, such as adenosquamous carcinoma and SCC. They collected the dataset at the University of California, Irvine (UCI) repository, and the Borderline-SMOTE approach was employed to balance the unbalanced data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On model evaluation, it was observed that the tree-based models trained by Borderline SMOTE were more reliable than other deployed models. In this research, we aim to create classification pipelines and provide interpretability for the predictions made [34] . For explaining various classifiers, we utilized various XAI tools such as Shapley Additive Explanations, Local Interpretable Model-Agonistic Explanations, Quantum Lattice, ELI5, and Anchor.…”
Section: Resultsmentioning
confidence: 99%
“…In [ 22 ], DT with Gini importance recorded an ACC of 92.59. In [ 25 ], multi-stack of ML recorded an ACC of 98.…”
Section: Discussionmentioning
confidence: 99%
“…In [ 25 ], the authors used ML models: LR, DT, RF, SVM, NB, KNN, AdaBoost, XGBoost, and Extratrees and DL and proposed multi-stacking ML to predict PCOS. They used Explainable AI (XAI) techniques to make model predictions understandable, interpretable, and trustworthy.…”
Section: Related Workmentioning
confidence: 99%